GSDME in cardiovascular diseases: research system and contemporary progress - Yang, Zhenzhen; Luo, Zilong; Zhang, Han; Zong, Junjie; Huang, Pinyan; Niu, Yuqing; Zhou, Cheng; Wang, Song; Zhang, Dan (Frontiers in Immunology, 2026)
Despite considerable advancements in treatment technologies in recent years, cardiovascular diseases still pose a significant threat to human health. Pyroptosis is a novel type of regulated cell death (RCD) associated with inflammation and innate immunity. Gasdermin E (GSDME), a key member of the gasdermin family, serves as a critical mediator of pyroptosis. Upon recognizing cellular stress or damage, GSDME can be activated through the classic caspase-3 cleavage pathway, releasing its N-terminal domain, which forms pores in the cell membrane to mediate pyroptosis and promote the release of inflammatory cytokines. Increasing evidence suggests that this process is closely associated with the progression of cardiovascular diseases, including atherosclerosis, myocardial infarction, nonischemic cardiomyopathy, and pulmonary arterial hypertension. These findings highlight the therapeutic potential of GSDME, with strategies targeting GSDME showing promising preclinical prospects. In this review, we introduce the structure and biological functions of GSDME, provide a brief overview of research strategies and experimental systems, and discuss recent scientific advances regarding GSDME in cardiovascular diseases. In addition, we explore the challenges currently facing the field and future research directions. A deeper understanding of the molecular mechanisms of GSDME in the cardiovascular system will provide a theoretical basis for the development of novel therapeutic strategies.